Evaluación del análisis financiero como herramienta de gestión empresarial, para el crecimiento económico de la empresa de transportes Ave Fénix, periodo 2013. - Rios Carbajal, Juan Jesús (2013)
Evaluation was performed Financial Analysis of Transportation Company Phoenix SAC, of the city of Trujillo, in order to generate economic growth through identifying financial risks own institutional operational activity. For what was done analyzing the structure and composition of the Statement of Financial Position and the Income Statement, as well as basic financial ratios of the company's services. Based on these results, Financial Analysis Assessment of Transportation Company Phoenix SAC, is a management tool for the efficient management decision-making on the part of management, and contributes to a better management of economic and financial resources. The implementation of a control system of economic resources through financial analysis, attached to procedures and technical processes, enables efficient and timely management of these resources, leading to the optimization and efficiency and effectiveness in management practice. Furthermore, it results the rational use of financial economic resources that lead to satisfaction and quality in the delivery of services to customers of the Company, strengthening institutional corporate image. Finally it is recommended that the management of the Company to implement the recommendations resulting from the research, to help improve administrative management, financial and economic, as well that is useful for decision-making.